PEMBEKALAN PRAKTEK KERJA INDUSTRI (PRAKERIN) DI SMK MUHAMMADIYAH 3 TERPADU - Rizaldi Putra; Pamuji Hari Santoso; Onny Setywan; Okalesa Okalesa; Ria Darmasari; Bord Nandre Aprila (JUDIKAT: Jurnal Pengabdian Kepada Masyarakat, 2023)
The form of this activity is to provide training to SMK students before participating in the Implementation of Industrial Work Practices (Prakerin), which is part of the Dual System Education which is an innovation in the SMK program where students carry out work practices (internships) in companies or industries that are part of the integral part of the education and training process in SMK. This activity was carried out at the Integrated 3 Muhammadiyah Vocational School by inviting lecturers from the Pelita Indonesia Institute of Business and Technology to provide material related to student preparation to take part in internships. This activity was held in early March 2023, while the purpose of holding this activity for Vocational High School (SMK) students is so that students can be prepared to improve quality and basic insights in the world of business or industry.